Remedial Reading Teacher to Reading Interventionist: The Evolution of a Profession and its Necessary Personality Traits - Savannah Sage Maydew (Educational Considerations, 2025)
This reflective article examines the work of Hurt, Roane, Simms, and Schell (1975), who surveyed remedial reading teachers to identify key personality traits essential to their profession. Their findings are contextualized within a broader historical framework, tracing significant educational policies and milestones that have shaped the field of reading intervention over the past 50 years. The article highlights both the enduring relevance and the evolution of these traits in the transition from "remedial reading teachers" to modern-day reading specialists. Drawing on practitioner insights, the author proposes additional traits necessary to meet the demands of contemporary literacy education.
Keywords: reading interventionist; reading specialist; remedial reading teacher; personality traits; soft skills